Mint and pomegranate extracts/oils as antibacterial agents against Escherichia coli O157:H7 and Listeria monocytogenes on shredded carrots - Xylia, Panayiota; Chrysargyris, Antonios; Botsaris, George; Tzortzakis, Nikos G. (My University, 2018)
Among minimally processed vegetables, shredded carrots are particularly popular. The aim of this study was to evaluate the antimicrobial activity of different washing treatments with aqueous solutions of mint essential oil (EO) (1:1000), mint hydrosol (1:10), and pomegranate juice (1:10) against two major foodborne pathogens on shredded carrots as well as their effect on carrot's quality. The results of this study indicate that the tested washing treatments resulted in a small but significant decrease of the microbial load of Escherichia coli and Listeria monocytogenes on the sixth day of storage. Pomegranate juice and mint hydrosol were more effective against L. monocytogenes, whereas mint EO was more effective against E. coli. Furthermore, an increase in carrot's total phenolics and antioxidants was observed with the application of mint hydrosol and pomegranate juice, whereas mint EO resulted in a decrease on the sixth day of storage. Additionally, a decreased chroma of the shredded carrots were observed during the application of mint hydrosol on the sixth day. Total carotenoids, ascorbic acid, total soluble solids, and tritratable acidity were not differing after six days of storage of shredded carrots. These washing products can be used for the partial disinfection of shredded carrots. Practical applications: Pomegranate and mint natural products solution can be used for the partial disinfection of minimally processed fresh produce as an alternative to chlorine, and these products can be a part of the sanitation process.
Keywords: Antimicrobial activity; Washing treatments; Mint essential oil; Mint hydrosol; Pomegranate juice